The impact of employee silence and organizational climate on job stress - Bülbül, Yasemin (My University, 2019)
Günümüz tüketim kültürü ve küresel pazar bizi insan faktörünün etkisini anlamaya ve analiz etmeye zorlamaktadır. Yoğunlaşan rekabet ve mücadele koşullarıyla, müşteri beklentilerini karşılamak ve çalışanların kalitesini artırmak, organizasyonel bir başarı değişikliği için, yaratıcılık, öğrenme ve yenilikçilik çalışanlar tarafından tetiklenen önemli faktörlerdir. Yeni yönetim teknikleri, çalışanların iş süreçlerine bilgi, fikir ve fikirleriyle katkıda bulunmaları gerektiğini öngörüyor. Ancak yapılan araştırmalar (Çakıcı, 2007, 2008; Morrison ve Milliken, 2000) bazı durumlarda çalışanların bilgi, fikir ve düşüncelerini çeşitli nedenlerle ifade etmediklerini göstermektedir. Çalışanların literatürdeki bu davranışı, çalışan sessizliği olarak tanımlanmaktadır. Çalışan sessizliği davranışı örgütte yaygınsa, o zaman örgütsel sessizliğe sahip bir iklim olduğu veya örgütsel iklimin bu sessizlik davranışından etkilendiği söylenebilir. Son olarak, karar alma ve ofis politikalarına çok az dâhil olmak üzere organizasyonel yapı ve iklim iş stresine neden olmaktadır (Beheshtifar, et al. 2013).Bu araştırmada örgütsel iklim ve çalışan sessizliği davranışının iş stresi algısı üzerindeki etkilerini analiz ettik. Araştırma modelini test etmek için demografik sorular içeren 54 ifadeden oluşan bir anket kullanılmıştır. Anket, İstanbul, Kocaeli ve Sivas'ta farklı pozisyonlarda birkaç farklı kamu kurumunda çalışan 342 kamu çalışanı tarafından dolduruldu. Veriler faktör analizi, güvenilirlik analizi, ortalama, standart sapma, Pearson korelasyon analizi ve doğrusal regresyon analizi ile analiz edildi. Araştırma sonucunda, Örgüt İklimi ile İş Stresi arasında alt boyutları da dahil olmak üzere anlamlı ilişkiler bulunmuştur. Ancak Çalışan Sessizliği ile İş Stresi arasında hiçbir ilişki yoktur ve benzer şekilde, Çalışan Sessizliği ile Örgütsel İklim arasında bir ilişki yoktur.

Today’s consumption culture and global market force us to understand and analyse the impact of the human factor. With the intensifying competition and combat conditions, to meet customer expectations and to increase the quality of the employees, for an organizational success change, creativity, learning and innovation are important factors which are triggered by employees. New management techniques predict that employees should contribute to the work processes with their knowledge, ideas and opinions. However, the researches (Çakıcı, 2007, 2008; Morrison and Milliken, 2000) show that employees in some conditions do not express their knowledge, ideas and opinions for several reasons. This behavior of the employees in the literature is defined as employee silence. If the employee silence behavior is widespread in the organization, then it can be said that there is a climate with organizational silence or organizational climate is affected by this silence behavior. Finally, Organizational structure and climate, including little involvement in decision-making and office politics cause work stress (Beheshtifar, et al. 2013). In this research we analyzed the impacts of the organizational climate and employee silence behavior upon work stress perception. A questionnaire consisting of 54 expressions including demographic questions was used in order to test the research model. The survey was filled out by 342 public sector employees who work in several different public institutions with different positions in Istanbul, Kocaeli and Sivas. Data was analyzed by factor analysis, reliability analysis, mean, standard deviation, Pearson’s correlation analysis, and linear regression analysis. As a result of the research, Meaningful relations were found between Organizational Climate and Work Stress including their subdimensions also. But there is no relationship between Employee Silence and Work Stress and similarly, there is no relationship between Employee Silence and Organizational Climate.
Keywords: Çalışan Sessizliği; Employee Silence; İş stresi; İş Stresi Organizational Climate; Job stress; Örgüt İklimi; Stres yönetimi; Stress management; Work Stress